An overview of the professional conditions of the football referees in Turkey - (:unkn) unknown (My University, 2015)
0

The aim and the question of this study is to present the variables and the processes of the football refereeing s professional conditions. Owing to the fact that there aren t any studies done before in the present literature relating to this matter, this study is summarized based on related instructions in Turkey, news from newspapers and examples from some countries in literature review section of this study. The method of the study is based on questionnaire technique. Due to the standardization in professional conditions and wages, questionnaire application is limited with Istanbul, and 55 male referees are found during the training in Istanbul Beylerbeyi Facilities. The subjects consist of the referees from 5 classifications and it is seen that the duration of experience increases form county refereeing to national refereeing. The referees are seen to conduct from 1 to 6 matches in a month. 44 of the subjects works in another job and insured through that job. This makes it obvious that the refereeing has not reached to the level of total professionalization. The fact that they remark 10.9% of the subjects are policemen, 12.7% of them are teacher, 14.5% of them are officer and 50.9% of them work in other lines of business and the rate of the ones who earn their livings only through refereeing corresponds to 3.6% validate the given situation. The fact that 50.9% of the subjects demand the refereeing to become a full-time profession testifies the request of the people who performs refereeing for professionalization. 50.9% of the subjects in total reported that Physical Aptitude Test causes stress. The fact that 36.3% of the subjects reported they do it as a hobby and 58% of them reported they do it both as a hobby and their own job exhibits the semi-professional appearance of football refereeing.
Keywords: Tarih